2019
DOI: 10.1177/0300060519892177
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 E670G polymorphism increases risk of coronary artery disease in a Chinese Han population

Abstract: Objective Coronary artery disease (CAD) is the leading cause of morbidity and mortality in the world. The proprotein convertase subtilisin/kexin type 9 ( PCSK9) E670G polymorphism has been reported to be associated with variability in levels of low density lipoprotein cholesterol, a risk factor for CAD. However, the relationship between PCSK9 E670G and CAD is still not fully elucidated. Methods A total of 225 patients and 189 control subjects were recruited in this study. DNA was extracted from peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Data were abstracted from 2,667 CAD cases and 2,817 controls ( Table 1 ) ( 4 16 ). Of the 21 articles obtained after the initial retrieval process, 13 were eligible for the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were abstracted from 2,667 CAD cases and 2,817 controls ( Table 1 ) ( 4 16 ). Of the 21 articles obtained after the initial retrieval process, 13 were eligible for the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 3, on the association of lipid parameters values change and PCSK9 gene E670G mutation in the CAD patients in the included individual studies, we could observe that compared with that in the AA genotype group, the serum TC and LDL-C levels in the GG genotype group were much higher (P < 0.05). Because the lipid parameters could not be found in Yang et al (6), Salazar et al (9), and Lin et al (16) studies, these data were not listed in Table 3. As the sample size in the GG genotype group was relatively small in some individual studies, even 0, the lipid parameters were analyzed in the AG+GG group together.…”
Section: Pooled Analysesmentioning
confidence: 99%
“…Additionally, PCSK9 gene polymorphism functions in regulation of serum lipid levels, 28 and it is mainly associated with some serum lipid parameters in the Han population 29 . It is also reported that PCSK9 E670G polymorphism is linked to CAD risk under different genetic models 30 . Recently, an E670G polymorphism of the exon 12 of the PCSK9 gene has been found to be involved in the severity of coronary atherosclerosis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…29 It is also reported that PCSK9 E670G polymorphism is linked to CAD risk under different genetic models. 30 Recently, an E670G polymorphism of the exon 12 of the PCSK9 gene has been found to be involved in the severity of coronary atherosclerosis. 31 Among patients with CHD, those carrying the G allele possessed elevated TC and TG levels compared with those with the AA genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Because only seven eligible studies in HWE were involved and only two genetic models were applied in their study, we believe that our study may offer a more objective result. In 2019, Lin et al got a similar conclusion on the association between PCSK9 gene E670G polymorphism and CAD by a meta-analysis (16). In their study, they did not exclude the literatures violating the HWE (21,22).…”
mentioning
confidence: 93%